MENINGKATKAN SOFTSKILL DAN MOTIVASI BELAJAR ANAK-ANAK PANTI ASUHAN MERCY CLEMENT INDONESIA MEDAN - Rivaldo Halomoan Sinaga; Randa Putra Kasea Sinaga; Fajar Utama Ritonga (CV SWA Anugerah, 2023)
Improving soft skills has an important role in supporting abilities and developing character in children. Apart from that, children must also have motivation to learn. The main problem with educational services at the Mercy Clement Indonesia Orphanage in Medan is that the limited number and educational background of the foster carers and older siblings are obstacles in providing guidance at the Orphanage. It is felt that the formal education received by foster children is not enough to improve children's soft skills and motivation to learn in facing the high demands on the quality of human resources today. The aim of this research activity is to improve the soft skills and learning motivation of children at the Mercy Clement Indonesia Medan orphanage to become children who are tough, enthusiastic in achieving their dreams, able to think critically, creatively and innovatively in dealing with all situations. The method for implementing this activity is presentation and lecture accompanied by discussion and question and answer between the orphanage children and the resource persons. The conclusion of the service activities that have been carried out is that the children of the Mercy Clement Indonesia Orphanage have a better understanding of how to improve their soft skills and become more motivated in learning and enthusiastic in achieving their dreams so that they become strong children, able to think critically, creatively and innovatively. in facing all situations, especially in the digital era.